Stress Concentration in the Bulk Cr2O3: Effects of Temperature and Point Defects - Mazharul M. Islam; Thierry Couvant; Philippe Marcus; Boubakar Diawara (Journal of Chemistry)
Modeling the growth and failure of passive oxide films formed on stainless steels is of general interest for the use of stainless steel as structural material and of special interest in the context of life time extension of light water reactors in nuclear power plants. Using the DFT+U approach, a theoretical investigation on the resistance to failure of the chromium-rich inner oxide layer formed at the surface of chromium-containing austenitic alloys (stainless steel and nickel based alloys) has been performed. The investigations were done for periodic bulk models. The data at the atomic scale were extrapolated by using the Universal Binding Energy Relationships (UBERs) model in order to estimate the mechanical behavior of a 10 μm thick oxide scale. The calculated stress values are in good agreement with experiments. Tensile stress for the bulk chromia was observed. The effects of temperature and structural defects on cracking were investigated. The possibility of cracking intensifies at high temperature compared to 0 K investigations. Higher susceptibility to cracking was observed in presence of defects compared to nondefective oxide, in agreement with experimental observation.